Rekonstruksi Pencatatan Perkawinan Berdasarkan Relevansi Antara Hukum Administrasi Negara dengan Hukum Administrasi Sipil - Emeralda, Nadya Rizki; Hamidah, Siti (Universitas Negeri Malang, 2022)
This study aimed to analyze the problems of enforcing civil administrative law in marriage registration and the concept of reconstructing marriage registration based on the relevance of state administrative law to civil administrative law. The method used in this study was normative juridical with a statutory approach and a conceptual approach. The problems of enforcing civil administration law in marriage registration include general problems related to administration, such as errors in identity writing and the organization of administrative institutions, which were full of personnel management problems. The reconstruction of marriage registration was based on the relevance between state administrative law and civil administrative law relating to the interests of public service delivery and institutional structure structuring in civil service law. The arrangement of personnel in the office of religious affairs need to pay attention to the employment law to create services based on professionalism in serving the community.